Persepsi Konsumen Terhadap Make Up Flawless Dalam Tata Rias Pengantin Modifikasi Di Mojokerto - Tsani, Talitha Yeshaya Nismara; Sri Usodoningtyas; Dindy Sinta Megasari; Mutimmatul Faidah (Program Studi Pendidikan Tata Rias, 2026)
Consumer and Makeup Artist (MUA) perceptions of flawless makeup in modified bridal makeup in Mojokertoshow a high level of appreciation. Consumers view this makeup style as capable of creating a natural,lightweight, and elegant appearance, making it in line with modern beauty trends without diminishing the charmof local culture. Meanwhile, MUAs see flawless makeup as an innovation that combines contemporary makeuptechniques with traditional touches, ensuring its relevance across various groups.This study aims to analyzepublic perception of flawless makeup in modified bridal makeup and to identify the factors that influenceconsumer interest in using the services of makeup artists (MUAs) in Mojokerto. The research employed aquantitative descriptive method, with data collected through a closed-ended questionnaire distributed to30 respondents, observations of five professional MUAs, and a literature review as supporting data. Data analysiswas conducted using SPSS software, including tests of validity, reliability, normality, heteroskedasticity, F-tests,and T-tests. The results indicate that consumers have a highly positive perception of flawless makeup. Consumerinterest is also high, influenced by the visual appeal of the makeup, effective promotion through social media, andthe quality of MUA services. Flawless makeup is perceived not only as enhancing the bride’s appearance but alsoas aligning with cultural values and the personal needs of modern brides. This study is expected to providepractical contributions for MUAs in developing service strategies and to serve as a scholarly reference for furtherresearch in the field of contemporary makeup and beauty